O negacionismo na oposição de jair bolsonaro à comissão nacional da verdade - Almada, Pablo Emanuel Romero [UNESP] (FapUNIFESP (SciELO), 2021)
This article analyzes the speeches made by then Federal Congressperson Jair Bolsonaro regarding Law No. 12,528/2011, which established the National Truth Commission (NTC). It is understood that these speeches, given in the Chamber of Deputies and in the National Congress, are essential for the understanding of the negative political language concerning the Brazilian civil-military dictatorship and the conflicts raised by memory recognition. We debate how these speeches reiterate the permanence of an authoritarian past, through attempts to manipulate the past and construct altered versions of the facts in the present. The research goes on to highlight arguments for the defense of a civil-military dictatorship and the left’s association with crime, concluding by reflecting on its support from 1964 press views.
Negationism in jair bolsonaro’s opposition to the national truth commission
Le négationnisme dans l’opposition de jair bolsonaro à la commission nationale de la véritÉ
Keywords: Armed Struggle; Civil-Military Dictatorship; Comissão Nacional da Verdade; Commission nationale de la vérité; dictature civile-militaire; Ditadura Civil-Militar; Jair Bolsonaro; Luta Armada; lutte armée; National Truth Commission; Negacionismo; Negationism; négationnisme